Internal Audit and Financial Performance of Cooperative Unions in Uganda:a Case Study of Bugisu Cooperative Union - Wolayo Esther (Uganda Christian University, 2024)
Financial performance determines the competitive advantage of the manufacturing company on the market. The study examined the relationship between internal audit and financial performance in manufacturing companies in Uganda, a case of Bugisu Cooperative Unions (BCU). Internal audit function is strategy to boost the strength of the internal control activities to achieve financial performance which requires empirical assessment. The study was guided with three research objectives which include; to examine the relationship between internal audit objectivity and financial performance of BCU; to analyze the relationship between internal audit independence and financial performance of BCU and to examine the relationship between internal audit competence and financial performance of BCU. The study adopted a cross-sectional study design with qualitative and quantitative approach. The unit of analysis was BCU and units of inquiry were employees at BCU. Primary data was collected from 73 filled questionnaires analyzed with SPSS V. 22 and 8 interviews conducted following Standard Operating Procedures to prevent spread of Covid-19. Given the nature of research objectives and questions, parametric test was carried out, specifically Pearson correlation to test the of each variable in explaining financial performance. Results revealed that BCU has internal audit department with competent staff who undertakes duties with independence and objectivity to observe over the operations and controls in activities to achieve financial performance at the company. Correlation analysis revealed that internal audit objectivity with correlation coefficient of 0.798**, internal audit independence with correlation coefficient of 0.854**, internal audit competence with correlation coefficient 0.654** have positive significant relationship on the financial performance of BCU. The study concluded that internal audit objectivity and independence are fundamental principles with positive significant relationship and effect to enhance orderly operations, risk assessment and evaluation of control activities to achieve financial performance. The study recommends that internal audit should be objective and independent to undertake activities, evaluation of internal controls, detection of errors and fraud, continuous appraisal of the process to sanction corrective measures to management to achieve financial performance.